Ondas de interiorização do profissionalismo médico e o desenvolvimento em São Carlos - Almeida, Fabio de Oliveira (Universidade Federal de São Carlos, 2016)
This research analyzed, in the local power of São Carlos (SP), the connections between medical professionalism, urban and industrial development and the political centralization of the Brazilian nation state, which conditioned specific waves of interiorization of medical professionalism, as well as particular professional rip current. The focus is oriented to the period of 1889 to 1988, when have occurred three waves of interiorization of medical professionalism and two professional rip currents. The first wave (1889-1930) happened at the beginning of the Republic, in the context of a decentralized political system (coronelismo) and of a parallel growth of the São Carlos’ coffee production. This allowed the first impulse of the local urban economy, the emergence of some new public health and medical assistance services and the establishment of an initial but effective medical market. Some new physicians arrived in the locality, whose specialization was commonly in general practice. Very soon, these professionals were integrated into the local social stratification, working as liberal professionals and in the Santa Casa de Misericórdia de São Carlos. The second wave (1948-1966) was characterized by the local effects of the political centralization of the state and its new role in the Brazilian urban and industrial development as well as in the organization of a national health system. The preview alliance between physicians and the São Carlos’ coffee elite became less important than in the past. The central state became more powerful and begun to compete with the local elites in the countryside of Brazil. This is the moment of the medical reaction to the socialization of medicine, when local physicians create the Sociedade Médica de São Carlos. In this period, there was an important historical trend of young local citizens (born in São Carlos), who went out to study medicine, but returning back later to work as physicians. As their antecessors, these young professional worked in the general practice. Otherwise, the third wave (1970-1988) arose since the reaction of physicians against some problems with the medical assistance of the state pension system. Indeed, the period also verified the organization of a new hospital, Casa de Saúde e Maternidade São Carlos, as well as the construction of a new building for Santa Casa de Misericórdia. São Carlos observed a relevant urban and industrial growth, paralleled by the increase of groups of industrial workers and urban middle classes. Aside the interiorization of medical faculties, professionals who have studied in these new faculties arrived São Carlos, not to act in general practice, but as specialists. Since a tied and smaller medical market as well as the condition of exporter of patients, São Carlos became polo of attraction for professionals and patients from other localities. This favored the creation and expansion of the UNIMED São Carlos, which responded to the higher demand for local medical services, the crisis in the medical assistance of the pension system and new obstacles from the market of private medical group sector. Both UFSCar and USP São Carlos intertwined with the growth of the locality, as well as with physicians, in order to increase the hospital services of São Carlos. As professional rip currents, between the first and the second waves, and between this one and the third wave, some reverse social processes acted historically in an opposite way in relation to each mentioned wave, favoring the occurrence of the next one. At the end of this period, emerged a combination of historical factors, such as: increase of the medical group sector (specially the UNIMED); the worst of the state medical assistance; political movements of physicians; emergence of the collective health; different role of industries in the Brazilian development; democratization; and decentralization of the national health system, which led to the creation of SUS.
Keywords: Interiorização do profissionalismo médico; Desenvolvimento; Urbanização; Industrialização; Centralização política do estado; Waves of interiorization; Medical professionalism; Local power; CIENCIAS HUMANAS::SOCIOLOGIA